Almost 20 years of Cyclone; past, present and future - Alexandre Torres Porres; Matt Barber; Derek Kwan (Revista Vortex, 2021)
This paper discusses the history of the Cyclone library, whose purpose is to clone MAX/MSP objects into Pure Data and provide compatibility between these two environments. This paper describes the different phases and versions of Cyclone from its early days to the current state of development and our future plans.